Digital Instructional Transformation: Enhancing Undergraduate Mathematical Connection Skills through Numeracy-Infused Flipbook Media - Novita Hendrawati; Gilang Ary Sandy; Rendy Ahmad Setiawan (CV. Bimbingan Belajar Assyfa, 2026)
Mathematical connection is a vital competence for undergraduate students to associate concepts within mathematics and across other disciplines, yet students frequently struggle to link mathematical ideas during problem-solving. This study aimed to develop a numeracy-infused flipbook as an innovative instructional medium to improve mathematical connection skills. Employing the 4-D (Define, Design, Develop, Disseminate) research and development model, this study involved 18 undergraduate students at STKIP Muhammadiyah Manokwari. The development process integrated numeracy-rich content, validated by experts in media, instructional design, and language, and deemed appropriate for learning implementation. Findings revealed that 72.22% of students achieved excellent mastery in solving numeracy-based problems, and the media achieved an 89.7% effectiveness score in enhancing student learning engagement. The study concludes that the developed flipbook is a valid, practical, and effective instructional tool for fostering mathematical connections. These results suggest that integrating numeracy literacy into digital learning ecosystems significantly supports the Scholarship of Teaching and Learning (SoTL) in higher education by providing an evidence-based pathway to transform technical mathematical content into interactive media.